Evaluating quality of care for patients with rotator cuff disorders - Breda H.F. Eubank; Mark R. Lafave; J. Preston Wiley; David M. Sheps; Aaron J. Bois; Nicholas G. Mohtadi (BMC, 2018)
Abstract Background Measuring quality in healthcare is vital in evaluating patient outcomes and system performance. The availability of reliable and valid information about the quality of care for patients presenting with rotator cuff disorders (RCD) in Alberta, Canada is scarce. The objective of this study is to measure quality of care for patients with RCD in order to identify areas of improvement. Methods This study employs descriptive survey research design. Between March 2015 and November 2016, a convenience sample of patients presenting with chronic, full-thickness rotator cuff tears to two sport medicine centres in Calgary and Edmonton, Alberta completed two questionnaires: the Healthcare Access and Patient Satisfaction Questionnaire (HAPSQ) and the Rotator Cuff Quality-of-Life Index (RC-QOL). Data collected using both questionnaires were used to make judgments about quality of care. Quality of care was evaluated using six dimensions of quality defined by the Alberta Quality Matrix for Health: accessibility, acceptability, efficiency, effectiveness, appropriateness, and safety. Data was also used to compare current patient clinical pathways to ideal clinical pathway algorithms and used to make judgments about the appropriateness and safety of healthcare practices. Results One hundred seventy-one patients participated in the study. The longest mean waiting times for medical services in Alberta were for magnetic resonance imaging (MRI) received in the public sector (103 days) and consultation by orthopaedic surgeon (172 days). Patient satisfaction with respect to quality of care was lowest for emergency room physician and highest for orthopaedic surgeon visits. Patients were treated by a mean of 2.5 physicians (SD: 0.77, range: 2-7). The total aggregate average cost per patient was $4541.19. The mean RC-QOL score for all patients was 42 (SD: 22). Only 54 patients (64%) requiring surgery were able to consult with a surgeon within benchmark timeframes. A comparison of current to ideal clinical pathway algorithms found that 38 patients (22%) experienced indirect clinical pathways, whereby care was fragmented and patients received care from multiple and often, redundant healthcare professionals. Conclusion There is a discrepancy between current and ideal clinical pathways whereby some patients are experiencing quality of care that is inefficient, disjointed, and less than ideal.